MALARIA KONGENITAL - Sri Wahyunie S; Nurhayana Sennang; D. Daud; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Congenital Malaria is an infectious disease caused by the malaria parasite that is transmitted from mother to child through theplacenta during pregnancy or at delivery. Clinical manifestations which may arise due to Plasmodium infection are: the irritability,fever, anaemia, jaundice and hepatosplenomegaly. The incidence of congenital malaria according to the National Basic Health Research2010 is only about 0.3%. Forty two days old male baby with the main complaints fever and pale since he was three (3) weeks old. Fromthe physical examination the reviewer found anaemia, jaundice and splenomegaly. Plasmodium vivax was detected by serologic andmicroscopic examination. From the pregnancy history of mother the reviewer found that at the age of seven (7) months of pregnancyshe suffered from malaria caused by Plasmodium vivax the same as the type of Plasmodium infected the baby. The baby was born innon malaria endemic area which enhanced the diagnosis of congenital malaria of this patient. The patient was fully recovered aftertreated with dehydroartemisin piperaquin and the reviewer reported one case of congenital malaria, forty twodays old male baby. Thediagnosis was made based on the malaria history of mother at seven (7) month of pregnancy, the serologic and microscopic examinationfrom the patient blood and the baby was born in a non malaria endemic area. The prognosis of patient with congenital malaria causedby Plasmodium vivax generally was good. The clinical condition was improved and fully recovered after treated with dehydro-artemisinpiperaquin.